Legal nature of spontaneous construction as a complex category: questions of theory and practice - V. I. Teremetskyi; S. A. Maliar (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the problems of spontaneous construction in comparing the public interest in ensuring the sustainability of civil turnover, the introduction of as much property as possible through the elimination of certain defective legal regimes, as well as private interests of landowners, developers and some other participants in civil turnover (customers, contractors, equity investors, etc.). The approach to defining the essence of unauthorized construction as a way to acquire ownership of certain real estate, which has certain defects in the identification process, as well as in terms of behavioral and object perception of this legal phenomenon is determined.